Italy : Technical Note on Financial Risk Management and Supervision of Cassa Di Compensazione e Garanzia S.P.A. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Note analyzes financial risk management and supervision of Cassa Di Compensazione e Garanzia S.P.A. (CC and G) in Italy. CC and G, the Italian central counterparty (CCP), is systemically important for the Italian market, and through the link with the French CCP, it is also relevant in terms of cross-border financial stability. CC and G's financial risk management framework is being improved further to comply with European Market Infrastructure Regulation (EMIR) requirements. The main changes that CC and G needs to implement include higher 'skin in the game' resources, the introduction of concentration limits on collateral, the reform of its liquidity management and of its investment policy, and introduction of individual client account segregation.